STRENGTHENING TASAWUF MATERIALS FOR THE COMMUNITY OF PAKAL VILLAGE, SURABAYA - Abdulloh Arif Mukhlas; Barudin (International Journal of Multidisciplinary Reseach, 2025)
This mentoring program, aimed at enhancing the piety of the community through routine study of tasawuf (Islamic mysticism) materials, was conducted in Pakal, Surabaya. The village already appears religious in its community. This is evident in daily activities, with congregational prayers at the mosque, religious organizations and assemblies running well. The activity in this mentoring program focuses on deepening tasawuf materials, so that worship activities and religious organizational activities are not merely carried out according to rules, but are understood from their philosophical values. This will shape the character of a community capable of embodying worship values. The mentoring began with observation of the Pakal Surabaya village community, followed by deepening using the PAR (Participatory Action Research) community service method. Participatory Action Research is a research model whose steps involve seeking something related to processes that connect research with social change processes. The results of this mentoring are expected to help the community become sincere in worship and serving the community, courteous and not arrogant in interactions, and able to cooperate and support each other.